Management of the Terrible Triad Injury of the Elbow: A Case Series Retrospective Review - Cruz-Calvente, Carmen; Nieto-Blasco, Javier; Fernández-Cuadros, Marcos E.; Fernández-Palacio, Pelayo; García-García, Javier; Blanco-Blanco, Juan Fco (International Journal of Orthopedics and Rehabilitation, 2016)
Objectives: To expose our experience in the multidisciplinary management of patients with terrible triad injury of the elbow (TTIE) treated in our hospital. Material and methods: A descriptive-retrospective study including all patients with TTIE treated surgically between January/2008-December/2014. The analyzed variables were demographic, etiologic, type of fracture (Mason, Reagan and Morrey Scale), type of surgery/approaching technique, time between injury-surgery, immobilization period, range-of-movement (ROM) before/after treatment, and complications. An assessment before/after the treatment using analogical visual scale (AVS), goniometry and Mayo Elbow Performance Index (MEPI) was carried out. Results: A total of 12 patients were included. The most common cause was accidental fall (75%). All fractures were surgically treated (mean 4.6 days after injury) with subsequent detention (29 days average). The surgical approach was lateral (n=8), posterior (n=2), and both lateral and medial (n=2). The increase in the flexion/extension ROM was 27.27º/24.09º, in pronation/supination was 23.65º/23.9º. The initial/final AVS was 4.46/2.16. In MEPI scale, 9 patients had excellent-good results, 2 regular, and one underwent bad response. Only one patient had complications during the follow up period. All patients were treated surgically promptly and immobilized for a month. As the MEPI states, the results of our series are acceptable. This is in accordance with present day reports. Conclusions: The clinical results of the series are consistent in relation to the literature. The results suggest that an integral, multidisciplinary approach (surgical and rehabilitation) for the TTIE must be achieved. Despite the small series and the infrequent appearance of the pathology, no cases were lost during the study.